ANALISIS HUBUNGAN KEPATUHAN DOKUMENTASI DISCHARGE PLANNING DENGAN LAMA RAWAT INAP DAN READMISI PADA PASIEN STROKE DAN CEDERA KEPALA DI RUMAH SAKIT AWAL BROS PEKANBARU - Ruth Hutagalung; Helen Andriani (LPPM Universitas Awal Bros, 2026)
Stroke and traumatic brain injury are commonly associated with prolonged hospital stay and readmission. Effective discharge planning is essential to ensure continuity of care; however, documentation compliance remains suboptimal. The objective of this research is to examine the association between discharge planning documentation compliance based on the METHOD and IDEAL models and length of hospital stay and 30-day readmission among stroke and traumatic brain injury patients. A quantitative analytical observational study with a retrospective cross-sectional design was conducted using medical records of 111 stroke and traumatic brain injury patients admitted to Awal Bros Hospital Pekanbaru between October and December 2025. Data were analyzed using Spearman's correlation, Mann–Whitney U, Kruskal–Wallis, multiple linear regression, and logistic regression. Source triangulation through confirmatory interviews with healthcare professionals was performed to validate discharge planning implementation. Poor discharge planning documentation was identified in 51.4% of the METHOD model and 44.1% of the IDEAL model. The IDEAL score showed a weak positive association with length of hospital stay (r=0.194; p=0.042), whereas the METHOD score was not significant. Neither model was associated with 30-day readmission (p>0.05). Comorbidity and complete functional dependence were significant predictors of prolonged hospitalization. Source triangulation confirmed that discharge planning was routinely implemented, although documentation remained incomplete, particularly in patient education, medication management, and dietary counseling. Discharge planning documentation showed a weak association with length of hospital stay but not with 30-day readmission. Strengthening documentation quality and multidisciplinary coordination is essential to improve continuity of care.